Luminescent High‐Mobility 2D Organic Semiconductor Single Crystals. (11th March 2022) - Fedorenko, Roman S.; Kuevda, Alexey V.; Trukhanov, Vasiliy A.; Konstantinov, Vladislav G.; Sosorev, Andrey Yu.; Sonina, Alina A.; Kazantsev, Maxim S.; Surin, Nikolay M.; Grigorian, Souren; Borshchev, Oleg V.; Ponomarenko, Sergey A.; Paraschuk, Dmitry Yu.
Abstract: 2D organic semiconductor single crystals comprising one or a few molecular layers of macroscopic lateral sizes are ideal materials for ultrathin, flexible, and transparent field‐effect devices—a platform for transistors and sensors. In recent years, these 2D materials have demonstrated high performance not inferior to their 3D counterparts. However, light emissive properties of 2D organic semiconductor single crystals have not yet been reported, and a combination of high charge‐carrier mobility and bright luminescence in one material is still a challenge for 2D organic optoelectronics. Emissive high‐mobility 2D organic semiconductor based on a [1]benzothieno[3, 2‐b]benzothiophene (BTBT)‐derivative, 2, 7‐bis(4‐decylphenyl)[1]benzothieno[3, 2‐b][1]benzothiophene (DPBTBT), is presented here. DPBTBT molecules self‐organize in large‐area ultrathin single‐crystalline films consisting of one or a few molecular layers. These 2D single crystals perfectly suit as an active layer of organic field‐effect transistors in full accordance with Shockley's model and uniquely combine the high charge‐carrier mobility reaching 7.5 cm 2  V –1  s –1 with prominent light emissive properties, which allow a demonstration of the first 2D organic light‐emitting transistor. The high charge‐carrier mobility and thermal stability of the crystalline phases, pronounced luminescence, and good shelf‐life stability suggest that emissive BTBT‐type molecules are a promising avenue for 2D organic optoelectronics. Abstract : Combination of high charge‐carrier mobility and light emission in a 2D organic material is a challenge. A novel strongly luminescent [1]benzothieno[3, 2‐b]benzothiophene derivative is synthesized and solution‐processed into large‐area 2D single crystals. The 2D crystals show high charge‐carrier mobility at the level of their best 3D counterparts and serve as an active layer in the first 2D organic light‐emitting transistor.